2020
DOI: 10.1503/cjs.006719
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass index affect the rate of adverse outcomes in total hip and knee arthroplasty? A retrospective review of a total joint replacement database

Abstract: Background: Total hip arthroplasty (THA) and total knee arthroplasty (TKA) are reliable surgical options to treat pain and disability resulting from degenerative conditions around the hip and knee. Obesity is a modifiable risk factor that contributes to significant morbidity. The purpose of this study was to retrospectively compare outcomes in primary hip and knee arthroplasty for patients with increased body mass index (BMI) and those with normal BMI, using data from the registry of the Alberta Bone and Joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…Using two, five, and 10 years as time points to quantify how many patients underwent a revision, we found that obese patients had significantly more revisions across all time points, consistent with past studies. 36,37 Revisions can be caused by various complications, however the most common is periprosthetic joint infection. 38 The PearlDiver database does not allow for investigating the specific causes of revision in either the obese or non-obese group.…”
Section: Discussionmentioning
confidence: 99%
“…Using two, five, and 10 years as time points to quantify how many patients underwent a revision, we found that obese patients had significantly more revisions across all time points, consistent with past studies. 36,37 Revisions can be caused by various complications, however the most common is periprosthetic joint infection. 38 The PearlDiver database does not allow for investigating the specific causes of revision in either the obese or non-obese group.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is known as a major risk factor for complications and impaired clinical outcome following different types of knee surgery [ 1 , 15 ]. Registry-based data have indicated higher complication rates in overweight patients after total knee arthroplasty and particularly in frequent periprosthetic joint infections [ 1 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is known as a major risk factor for complications and impaired clinical outcome following different types of knee surgery [ 1 , 15 ]. Registry-based data have indicated higher complication rates in overweight patients after total knee arthroplasty and particularly in frequent periprosthetic joint infections [ 1 , 36 ]. Studies on unicompartmental knee arthroplasty have found a fivefold increase in failure rate in morbidly obese patients due to disease progression in other compartments or mobile bearing instability [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…From an orthopaedic perspective, the increased risk of perioperative complications associated with obesity has been described by Abdulla et al in 2020 in both TKR and THR patients. The authors highlighted that, in this patient group, increase in BMI was associated with increased inpatient medical events and 30-day readmission rates when compared to those patients who were of a normal BMI [13]. Xu et al have further shown that rates of wound infection also correlated with increases in BMI in the total joint arthroplasty cohort [14].…”
Section: Discussionmentioning
confidence: 94%